A {112}Σ3 grain boundary generated from the decomposition of a Σ9 grain boundary in multicrystalline silicon during directional solidification. (1st July 2019) - Chuang, Lu-Chung; Maeda, Kensaku; Shiga, Keiji; Morito, Haruhiko; Fujiwara, Kozo
Abstract: The generation of a {112}Σ3 grain boundary (GB) was observed in situ from the decomposition of a Σ9 GB during directional solidification of multicrystalline Si. A faceted groove formed at the junction of the solid/melt interface and the {112}Σ3 GB. This mechanism is different from that for the growth of {111}Σ3 GBs, for which no groove formed at the interface. If the growth rates for the adjacent facets of the groove are the same, the GB can grow in a straight manner along the {112} plane. The present results suggest that kinetics can give rise to high-energy GBs during solidification. Graphical abstract: Unlabelled Image